Employers' Perceptions of Information Technology Competency Requirements for Management Accounting Graduates - Spraakman,Gary; O’Grady,Winifred; Askarany,Davood; Akroyd,Chris (Accounting Education, 2015)
Management accountants work in a computerized workplace with information technology (IT) being used for financial ledgers and reporting. Thus, the role of the management accountant has shifted from capturing and recording transactions to analyzing business issues. This paper examines the IT knowledge and skills that employers require of management accounting graduates. An exploratory field research approach was used to gather data. Chief financial officers (CFOs) and their subordinates at some of New Zealand’s largest firms were interviewed. These respondents were consistent in their requirements. In particular they emphasized intermediate proficiency with some Microsoft tools (Excel, Word, PowerPoint, and Outlook) and familiarity with the structure and navigation of an enterprise resource planning (ERP) system to be able to process transactions such as accounts receivable or accounts payable. Of those requirements, Excel for analysis was by far the most important. Our contributions update and augment the literature by clarifying the perceptions of employers regarding the IT competencies required of management accounting graduates.
Keywords: Accounting